About the Methods of General treatment. Blood Vessels for Bloodletting in the Teachings of IbnSina (Global Journal of Medical Research, 2022)
Abstract not found
Keywords: nutrition; food; medicine; hand action; relaxation; nature; dry; hot; cold; wet; IbnSina